The Yersinia Phage X1 Administered Orally Efficiently Protects a Murine Chronic Enteritis Model Against Yersinia enterocolitica Infection - Xue, Yibing; Zhai, Shengjie; Wang, Zijing; Ji, Yalu; Wang, Gang; Wang, Tianqi; Wang, Xinwu; Xi, Hengyu; Cai, Ruopeng; Zhao, Rihong; Zhang, Hao; Bi, Lanting; et al. (Frontiers in Microbiology, 2020)
Yersinia enterocolitica (Y. enterocolitica) is generally considered an important food-borne pathogen worldwide, especially in the European Union. A lytic Yersinia phage X1 (Viruses; dsDNA viruses, no RNA stage; Caudovirales; Myoviridae; Ackermanviridae family) was isolated. Phage X1 showed a broad host range and could effectively lyse 27/51 Y. enterocolitica strains covering various serotypes that cause yersiniosis in humans and animals (such as serotype O3 and serotype O8). The genome of this phage was sequenced and analysed. No toxin, antibiotic-resistance or lysogeny related modules were found in the genome of phage X1. Studies of phage stability confirmed that X1 had a high tolerance towards a broad range of temperatures (4-60°C) and pH values (4-11) for 1h. The ability to resist harsh acidic conditions and enzymatic degradation in vitro demonstrated that phage X1 is suitable for oral administration, and in particular, that this phage can pass the stomach barrier and efficiently reach the intestine in vivo without losing infectious ability. The potential of this phage against Y. enterocolitica infection in vitro was studied. In animal experiments, a single oral administration of phage X1 at 6 h post infection was sufficient to eliminate Y. enterocolitica in 33.3% of mice (15/45). In addition, the number of Y. enterocolitica strains in the mice was also dramatically reduced to approximately 103 CFU/g after 18 h compared with 107 CFU/g in the mice without phage treatment. Treatment with phage X1 showed significant improvement by intestinal histopathologic observations. Moreover, proinflammatory cytokine levels (IL-6, TNF-α and IL-1β) were significantly reduced (P < 0.05). These results indicate that phage X1 is a promising candidate to control infection by Y. enterocolitica in vivo.